Streams and stages: Reconciling Kingdon and policy process theory. (31st July 2014) - Howlett, Michael; McConnell, Allan; Perl, Anthony
Abstract Use of metaphors is a staple feature of how we understand policy processes – none more so than the use of 'policy stages'/'cycles' and 'multiple streams'. Yet even allowing for the necessary parsimony of metaphors, the former is often criticised for its lack of 'real world' engagement with agency, power, ideology, turbulence and complexity, while the latter focuses only on agenda‐setting but at times has been utilised, with limited results, to understand later stages of the policy process. This article seeks to explore and advance the opportunities for combining both and applying them to the policy‐formation and decision‐making stages of policy making. In doing so it examines possible three, four and five stream models. It argues that a five stream confluence model provides the highest analytical value because it retains the simplicity of metaphors (combining elements of two of the most prominent models in policy studies) while also helping capture some of the more complex and subtle aspects of policy processes, including policy styles and nested systems of governance.